Numerical and experimental study of hydrofoil-flap arrangements for hydrokinetic turbine applications (2021)
In this work, the efficiency of two horizontal-axis hydrokinetic turbines, whose blades were designed with and without multi-element hydrofoil cross-sections, has been numerical and experimentally inves- tigated for tip speed ratio (k) values ranging between 2.5 and 9.0 to compare the experimental rotor per- formance with numerical results. The Eppler 420 hydrofoil was used for the design of the blades applying the blade element momentum (BEM) theory. The variation of the power coefficient curve of the turbines was analyzed by using computational fluid dynamics (CFD) and experimental tests through ANSYs Fluent software with six-degrees of freedom (6-DoF) user-defined function (UDF) method and an open hydraulic channel, respectively. Numerically, for the turbine with a multi-element hydrofoil and without a multi- element (traditional) hydrofoil, maximum power coefficients (CPmax) of 0.5050 and 0.419 (at a k value equal to 7.129 and 6.739, respectively) were obtained. It is worth noting that a reasonable agreement between the numerical and the experimental results was achieved. In this regard, the blade with a multi-element hydrofoil has a positive influence on the hydrokinetic turbine performance; therefore, it can be used for power generation in river or marine systems.